Pengembangan Sulam Gim Kebaya Pengantin Gaya Surakarta - Prihatina, Yuhri Inang; Guntur, Guntur; Rizali, Nanang (Acintya, 2023)
This research was motivated by the existence of gim embroidery as a Surakarta-style bridal kebaya ornament with all limitations, such as the lack of craftsmen, the high cost of yarn materials, and competition with other ornamental techniques that are more developed. The purpose of this study is to describe the development  of  gim  embroidery  on  Surakarta-style  bridal  kebaya.  The  method  used  is  a  qualitative grounded research model. Data were collected through interviews, observations, literature studies, artifact studies, and documentation. Data analysis is conducted interactively through data reduction, presentation, discussion, and conclusions. The results showed that the development of Surakarta-style bridal kebaya gim embroidery had at least three groups, namely the development of materials and techniques that still maintain motifs and patterns according to pakem, the development of motifs and designs that combine the characteristics of Surakarta style and Yogyakarta style, and the development of kebaya forms followed by the development of motifs and patterns. The development that was found can be used as a reference in the development of game embroidery not only in bridal kebayas but also in other forms of revitalization to preserve gim embroidery.Keywords: gim embroidery, Surakarta-style bridal kebaya, development concept.